Pre-emptive administration of intravenous acetaminophen with transversus abdominis plane block (tap-blocke) in the prevention of fentanil-induced hyperalgesia in pediatric oncological patient undergoing abdominal surgery - Dmytro Dmytriiev; Oleksandr Nazarchuk (Journal of Education, Health and Sport, 2015)
Dmytriiev Dmytro, Nazarchuk Oleksandr. Pre-emptive administration of intravenous acetaminophen with transversus abdominis plane block (tap-blocke) in the prevention of fentanil-induced hyperalgesia in pediatric oncological patient undergoing abdominal surgery. Journal of Education, Health and Sport. 2015;5(10):98-107. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32514